The Representation of Palestinian-Israeli Conflict in Online News Articles: A Critical Discourse Analysis - Adnania Nugra Heni; Oktiva Herry Chandra (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2022)
This study aims to analyse how Palestinian-Israeli conflicts are reported by two different news media, in this case Fox News (American) and Detik.Com (Indonesian). The data in this study were words and sentences which represent how Palestinian-Israeli conflict is reported by the two media. The data were taken from 4 news articles of Fox News and Detik.com which were reported from May 15 to May 31, 2021. The data were collected by using participant non-observation method with note-taking techniques. Then, the data were analyzed based on Critical Discourse Analysis (CDA) theory proposed by Fairclough (1995). The results of the research indicate that there are differences in the representation of Palestinian and Israeli conflicts in the two media. In Fox News articles, Palestine, especially Hamas, is represented as a terrorist and there is an element of the American government's alignment with Israel. Meanwhile, in Detik.com articles, Israel is represented as the perpetrator of the attack while Palestine is represented as the victim.